Diversity of Fungi Associated with Atta bisphaerica (Hymenoptera: Formicidae): The Activity of Aspergillus ochraceus and Beauveria bassiana - Myriam M. R. Ribeiro; Karina D. Amaral; Vanessa E. Seide; Bressane M. R. Souza; Terezinha M. C. Della Lucia; Maria Catarina M. Kasuya; Danival J. de Souza (Psyche: A Journal of Entomology)
The grass-cutting ant Atta bisphaerica is one of the most serious pests in several pastures and crops in Brazil. Fungal diseases are a constant threat to these large societies composed of millions of closely related individuals. We investigated the occurrence of filamentous fungi associated with the ant A. bisphaerica in a pasture area of Viçosa, Minas Gerais State, Brazil. Several fungi species were isolated from forager ants, and two of them, known as entomopathogenic, Beauveria bassiana and Aspergillus ochraceus, were tested against worker ants in the laboratory. The two species were highly virulent, achieving 50 percent worker mortality within 4-5 days. It is the first time A. ochraceus, a commonly found fungal species, is reported to infect Atta species at a high prevalence. Possible uses for the fungus within biological control are discussed.